Tracking the Origin and Early Evolution of Reptiles - Marchetti, Lorenzo; Voigt, Sebastian; Buchwitz, Michael; MacDougall, Mark J.; Lucas, Spencer G.; Fillmore, David L.; Stimson, Matthew R.; King, Olivia A.; Calder, John H.; Fröbisch, Jörg (Frontiers in Ecology and Evolution, 2021)
The origin of Reptilia and the biostratigraphic and palaeobiogeographic distribution of its early representatives are still poorly understood. An independent source of information may come from the extensive Carboniferous footprint record of reptiles, which is arguably richer and more complete than the skeletal record. Nevertheless, previous studies often failed to provide useful information because they were based on poorly preserved material and/or characters non-exclusive of reptile tracks. In fact, a large part of the supposed early reptile tracks can be assigned to the anamniote ichnotaxon Hylopus hardingi. Here, we revise the ichnotaxon Hylopus hardingi based on anatomy-consistent material, attribute it to anamniote reptiliomorphs, and distinguish it from Notalacerta missouriensis, the earliest ichnotaxon that can be attributed to reptiles, and the somewhat younger Varanopus microdactylus (attributed to parareptiles, such as bolosaurians) and Dromopus lacertoides (attributed to araeoscelid reptiles and non-varanodontine varanopids). These attributions are based on correlating morphofunctional features of tracks and skeletons. Multivariate analysis of trackway parameters indicates that the late Bashkirian Notalacerta missouriensis and Hylopus hardingi differ markedly in their trackway patterns from Late Mississippian Hylopus hardingi and Late Pennsylvanian reptile tracks, which appear to share a derived amniote-like type of gait. While the first occurrence/appearance of reptile tracks in the tetrapod footprint record during the late Bashkirian corresponds to the first occurrence/appearance of reptiles in the skeletal record, footprints significantly enlarge the paleobiogeographic distribution of the group, suggesting an earlier radiation of reptiles during the Bashkirian throughout North America and possibly North Africa. Dromopus appeared in the Kasimovian together with the diapsid group Araeoscelidia, but footprints from Western-European occurrences enlarge the paleobiogeographic distribution of diapsids and varanopids. Varanopus and bolosaurian parareptiles appear in the Gzhelian of North America. Older parareptiles are, however, known from the late Moscovian. In all, the footprint record of early reptiles supplements the skeletal record, suggesting possible future lines of research.